Investigating the molecular basis of biased signalling at cannabinoid receptors - Dennis, Morgan Jane (2023)
The endocannabinoid system (ECS) comprises both cannabinoid receptor 1 (CB1R) and cannabinoid receptor 2 (CB2R), which belong a class of rhodopsin-like G protein-couple receptors (GPCRs) alongside the endogenous ligands, and the respective enzymes for their synthesis and degradation. The ECS and cannabinoid receptors are involved in a number of important physiological processes both in the brain and peripheral tissues, including neuronal development, learning and memory formation, as well as immune cell function and inflammation. It has proven difficult to develop novel selective drugs for the cannabinoid receptors without causing multiple, and often serious, side-effects. In addition, GPCRs such as the cannabinoid receptors couple to one or more trimeric G proteins or arrestin proteins, adding more complexity to drug discovery efforts targeting these receptors. It is now firmly established that certain drugs can trigger pathway-specific signalling, which may enable the development of drugs with greater selectivity for therapeutic pathways and potentially with fewer side effects. We studied this phenomenon known as biased signalling at human cannabinoid receptors using a series of novel ligands, identified via in silico docking, and G protein biosensors. Initial competition and saturation binding assays characterised ligand binding to both CB1Rs and CB2Rs, while signalling bias investigated via bioluminescent resonance energy transfer (BRET)-based mini-G protein (which mimics a full-length G protein) and β-arrestin recruitment assays (receptor C-terminus tagged with NanoLuc™ donor fluorophore and β-arrestin tagged with a venus acceptor fluorophore). Functional cannabinoid receptor activation was then assessed using G protein activity (Gi-CASE) sensors that use BRET to report the activation-induced dissociation of the G protein. Among the three novel compounds investigated, two proved to be agonists and one an inverse agonist at CB1R and CB2R. Agonist activity in the Gi-CASE assays elicited a decrease in the BRET signal, indicative of receptor activation and G protein dissociation. Inverse agonist activity caused an increase in BRET signal, suggestive of receptor inactivation and the accumulation of inactive G protein. However, the novel ligands appeared relatively unbiased at the cannabinoid receptors due to similar recruitment of mini-G and β-arrestin proteins following receptor activation, both in terms of potency and efficacy. A more complete pharmacological profile of the reference and novel ligands was gained, using confocal microscopy and a diffusion-enhanced resonance energy transfer (DERET) assay, both used to evaluate agonist-induced receptor internalisation at the cannabinoid receptors. Developing drugs to target CB1R and CB2R is valuable because only a few marketed drugs currently target cannabinoid receptors. Rimonabant is a previously marketed CB1R antagonist and a potent anti-obesity agent, and is associated with significant neurological side effects, which eventually led to its withdrawal from the market. Rimonabant serves as an example of the challenges faced with the development of novel, safe drugs to target cannabinoid receptors in disease. Unfortunately, we did not identify any ligand bias among any of the three novel compounds under study. However, continued investigation of these and other novel compounds will better characterise their potential to become novel therapies for conditions linked with cannabinoid receptor signalling. Looking forward, we also highlight a novel membrane-based biosensor assay, a step towards creating a high-throughput means to identify novel hits at cannabinoid receptors.